Fabrication of Microbicidal Silver Nanoparticles: Green Synthesis and Implications in the Containment of Bacterial Biofilm on Orthodontal Appliances - Farheen, Saba; Oanz, Abdul M; Khan, Nazoora; Umar, Mohd Saad; Jamal, Fauzia; Altaf, Ishrat; Kashif, Mohammad; Alshameri, Ansam Wadia; Somavarapu, Satyanarayana; Wani, Irfan Ahmad; Khan, Saba; Owais, Mohammad (Frontiers in Nanotechnology, 2022)
Among various metal-based nanoparticles, silver nanoparticles (AgNPs) manifest superior inhibitory effects against several microorganisms. In fact, the AgNPs based treatment has been reported to inhibit both sensitive as well resistant isolates of bacteria and other disease-causing microbes with equal propensity. Keeping this fact into consideration, we executed bio-mediated synthesis of AgNPs employing extract of flower as well as various other parts (such as bud and leaf) of the Hibiscus rosa-sinensis plant (HRSP). The physicochemical characterization of as-synthesized AgNPs was executed employing transmission electron microscopy (TEM), dynamic light scattering (DLS), zeta-potential, fourier transform infrared spectroscopy (FT-IR), and UV-VIS spectroscopy, etc. The as-synthesized AgNPs demonstrated strong antimicrobial activity against both Gram-positive as well as Gram-negative bacteria with equal propensity. The as-synthesized AgNPs successfully inhibited Streptococcus mutans (S. mutans), one of the main causative bacteria responsible for dental caries. Considering the fact that orthodontic appliances facilitate infliction of the oral cavity with a range of microbes including S. mutans, we determined the growth inhibitory and anti-adherence activity of AgNPs on orthodontic appliances. We performed microbiological assays employing AgNPs adsorbed onto the surface of Nickel-Titanium (Ni-Ti) orthodontic wires. Topographic analysis of the de-contaminated Ni-Ti orthodontic wires was assessed by scanning electron microscopy. In addition to antimicrobial and antibiofilm activity against oral S. mutans, the as-fabricated AgNPs demonstrated significant inhibitory and anti-biofilm properties against other biofilm-forming bacteria such as Escherichia coli and Listeria monocytogenes as well.